(untitled) (Journal of Asian Development Studies, 2023)
Artificial Intelligence (AI)’s revolutionary impacts have transformed all sectors of the economy, including financial services. AI has brought a paradigm shift in increasing financial inclusion in an economy. Financial inclusion provides financial services to all segments of society according to their needs at affordable costs. It is an essential enabler of the sustainable development agenda set by the United Nations. The prosperity of countries is highly dependent on the level of financial inclusion, and AI plays a significant role in its achievement. This concept’s importance has grabbed researchers’ attention in the last decade. This paper presents a systematic literature review of scholarly research on implementing AI for financial inclusion. It began by reviewing two databases’ articles, includingEmerald and ScienceDirect. From this, the paper presents dimensions of research on AI and financial inclusion that researchers have explored. This systematic review finds significant concluding remarks. The literature explains the importance of AI in achieving financial inclusion, but there needs to be more AI and ML methodologies in research. The research identifies implications for future research and critical practice areas in AI and financial inclusion